Desigualdades. Propiedades - Cordova Pizan, Lita (2019)
The present work of Professional Proficiency sufficiency, is title Inequity. Properties (Z). The session was develop by the bibliographical references and other sources, moreover with the knowledges that igain by the develop of this and the years that spent in my academic formation. The understanding, analysis, and solving process about inequity. Properties (Z), will let vs get solutions to many problematic issues that we faced in our daily life, but at the same time we use values and cross cutting approaches._x000D_ The suggestion after to students the processes and algorithins in the application of the properties in the same way, teachers have the chance to learn a variety of possibilities to teach in many different strategies. This include tuition tools related with math learning processes, in which students live their prior knowledge for obtain the cognitive conflict by the discuss or many questions that analyze the challenging situation related with the motivation: in the develop of the session, the student use the properties relating, it the problematic issues and this will let the proof of theorems with the use of axioms and strategies of the case with arguing. Finally, we do a feedback.